2009
DOI: 10.1089/end.2009.0394
|View full text |Cite
|
Sign up to set email alerts
|

Skin to Stone Distance Is an Independent Predictor of Stone-Free Status Following Shockwave Lithotripsy

Abstract: SSD is an easily measured parameter on NCCT that independently correlates with SWL efficacy in treating stones in all locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 13 publications
2
49
0
5
Order By: Relevance
“…[3][4][5] Importantly, these outcomes remain favorable despite stone configuration, size, location, or composition, which stands in stark contrast to other surgical modalities, namely shock wave lithotripsy. 6,7 Over the past few decades, obesity, defined as a body mass index (BMI, kg/m 2 ) greater than 30, has become increasingly prevalent, reaching epidemic proportions. 8 Given the association between obesity, metabolic syndrome, and kidney stones, 9,10 these patients commonly present with large renal stones for which PCNL is the optimal surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Importantly, these outcomes remain favorable despite stone configuration, size, location, or composition, which stands in stark contrast to other surgical modalities, namely shock wave lithotripsy. 6,7 Over the past few decades, obesity, defined as a body mass index (BMI, kg/m 2 ) greater than 30, has become increasingly prevalent, reaching epidemic proportions. 8 Given the association between obesity, metabolic syndrome, and kidney stones, 9,10 these patients commonly present with large renal stones for which PCNL is the optimal surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the fact that SWL represents a highly successful non-invasive treatment in urolithiasis, several studies have demonstrated diminished efficacy in obese patients since this technique is considerably affected by skin-to-stone distances (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Так, нативная МСКТ, признанная «золотым стандар-том» в диагностике почечной колики, по точно-сти значительно превосходит внутривенную урографию, способна определять все типы кам-ней кроме индинавировых, их плотность, внут-реннюю структуру и анатомию интересующей области -все эти данные необходимы для вы-бора метода лечения [20][21][22][23][24][25].…”
unclassified
“…Таким обра-зом, только элементы с выраженной разницей в показателях Z будут различимы по их спек-тральным свойствам. Характеристиками этих различий являются: 1) Двухэнергетический индекс (ДЭИ) = (Х80-Х140)/(Х80+Х140+2000), где Х80 -плотность материала в HU при 80 kV, Х140 -плотность при 140 kV [24]. 2) Двухэнергетическое отношение (ДЭО) = (плотность материала на низкоэнергетическом изображении/плотность на высокоэнергетиче-ском изображении) [48].…”
unclassified